Challenges of adopting strategic procurement policies: a case study of infrastructure Development Company Limited - Islam, Md. Maidul (BRAC University, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Masters in Procurement and Supply Management, 2017.